Molding film for in-mold transfer, and method for producing molded article
By optimizing the composition and structure of the conductive layer in the molding film for in-mold transfer, the problems of internal deviation of the conductive layer and reduced electromagnetic wave shielding performance during the in-mold transfer molding process are solved, and the formability and electromagnetic wave shielding performance are improved.
Patent Information
- Application Number
- CN202380047153.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-16
- Filing Date
- 2023-05-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-05-16
AI Technical Summary
In the process of in-mold transfer molding, the in-conductive layer deviation, the electromagnetic wave shielding performance decreases, and the molded product is prone to cracks and cracks when it is complex in shape.
A molded film for in-mold transfer consisting of a base film, a release layer, and a conductive layer is used. The conductive layer contains not less than 60% and not more than 91% of particles, and not less than 9% and not more than 40% of resin. The weight of the resin is Average molecular weight is over 5000 And less than 10,000, the particles contain zero-valent metals such as carbon, silver, gold, etc., the thickness of the conductive layer is 5 μm or more and 15 μm or less, and the glass transition temperature of the conductive layer is controlled to be 40°C or more and 100°C or less during the molding process.
The improvement of excellent formability, after molding, and electromagnetic wave shielding performance improves, improves productivity, and reduces the internal deviation and crack risk of the conductive layer.
Smart Images

Figure BDA0005187381780000181 
Figure BDA0005187381780000191
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a molded film for in-mold transfer and a molded product. Background Art
[0002] In recent years, with the expansion of IoT society, the requirements for electromagnetic wave shielding performance have become increasingly higher in the fields of mobile phones, electrical products, and automobile parts. In the case of using resin for the frame, it is known to apply plating, conductive coating, and other treatments to the molded product. However, in these previous methods, since environmental countermeasures such as drainage treatment and solvent post-treatment are required, various attempts have been made to improve this.
[0003] For example, Patent Document 1 discloses a technique for in-mold transfer molding of a molding film having a conductive layer containing a resin and conductive fine particles. Patent Document 2 discloses a technique for in-mold transfer molding of a molding film having a conductor layer composed of a metal or a conductive polymer resin.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-192960
[0007] Patent Document 2: Japanese Patent Application Publication No. 2006-297642 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, the technology described in Patent Document 1 has problems in that the conductivity and electromagnetic wave shielding properties are deteriorated due to the in-plane deviation of the conductive layer when the in-mold transfer molding is performed. On the other hand, the technology described in Patent Document 2 has problems in that the conductive layer has cracks and breaks when the shape of the molded product is complicated.
[0010] The present invention aims to improve the problems of the prior art and provide a molded film for in-mold transfer having excellent moldability, conductivity after molding, and electromagnetic wave shielding properties and good productivity, and a method for producing a molded product.
[0011] Solutions to Solve Problems
[0012] The present invention has been studied intensively to solve the above-mentioned problems, and as a result, it has been found that the problems are solved as follows, thereby completing the present invention. That is, a preferred embodiment of the method for producing a molded film for in-mold transfer and a molded article of the present invention adopts the following configuration.
[0013] (1) A molded film for in-mold transfer, comprising, in order, a substrate film, a release layer, and a conductive layer, wherein the conductive layer contains 60% by mass or more and 91% by mass or less of particles in 100% by mass of the conductive layer, the conductive layer contains 9% by mass or more and 40% by mass or less of a resin, the weight average molecular weight of the resin is 5,000 or more and less than 10,000, and the particles contain one or more selected from zero-valent carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum.
[0014] (2) The molded film for in-mold transfer according to (1), wherein the conductive layer has a thickness of 5 μm or more and 15 μm or less.
[0015] (3) The molded film for in-mold transfer according to (1) or (2), wherein, for the conductive layer, when the temperature is increased from 20°C to 250°C at 20°C / min in a nitrogen atmosphere using a differential scanning calorimeter, a glass transition temperature is observed in the range of 40°C to 100°C.
[0016] (4) The molded film for in-mold transfer according to any one of (1) to (3), comprising the base film, the release layer, the conductive layer, and an adhesive layer in this order.
[0017] (5) The molded film for in-mold transfer according to any one of (1) to (4), wherein the release layer contains a silicone resin as a main component.
[0018] (6) The molded film for in-mold transfer according to (5), wherein the release layer contains an alkyd-modified silicone resin as a main component.
[0019] (7) The molded film for in-mold transfer according to any one of (1) to (6), wherein the resin is a polyester resin.
[0020] (8) The molded film for in-mold transfer according to (7), wherein the acid value of the polyester resin is 5 mgKOH / g or more and 20 mgKOH / g or less.
[0021] (9) The molded film for in-mold transfer according to any one of (1) to (8), wherein the particles are first particles having an aspect ratio of 1 or more and less than 2 and second particles having an aspect ratio of 2 or more.
[0022] (10) The molded film for in-mold transfer according to any one of (1) to (9), wherein the electromagnetic wave shielding effect of the molded film for in-mold transfer measured by a KEC method (electric field) using electromagnetic waves at a frequency of 300 MHz is 40 dB or more.
[0023] (11) The molded film for in-mold transfer according to any one of (1) to (10), wherein the base film is a polyethylene terephthalate film.
[0024] (12) A method for producing a molded article, comprising the steps of placing the molding film for in-mold transfer according to any one of (1) to (11) in a mold and then injecting a molding resin and / or a molding resin precursor.
[0025] Effects of the Invention
[0026] According to the present invention, it is possible to provide a molded film for in-mold transfer and a method for producing a molded product which are excellent in moldability, conductivity after molding, and electromagnetic wave shielding properties and have good productivity. DETAILED DESCRIPTION
[0027] A preferred embodiment of the molded film for in-mold transfer of the present invention is a molded film for in-mold transfer, which has a base film, a release layer, and a conductive layer in this order, wherein the conductive layer contains 60% by mass or more and 91% by mass or less of particles in 100% by mass of the conductive layer, the conductive layer contains 9% by mass or more and 40% by mass or less of a resin, the weight average molecular weight of the resin is 5000 or more and less than 10000, and the particles contain one or more selected from zero-valent carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum. The molded film for in-mold transfer of the present invention is specifically described below.
[0028] [Conductive layer]
[0029] In the present invention, a preferred embodiment of the conductive layer is that 60% to 91% by mass of particles are contained in 100% by mass of the conductive layer, and the conductive layer contains 9% to 40% by mass of resin. By adopting such an embodiment, even if the conductive layer is heated by molding, fine cracks will not be generated, and excellent moldability can be achieved.
[0030] Furthermore, by making the weight average molecular weight of the resin greater than or equal to 5,000 and less than 10,000, and making the aforementioned particles contain one or more selected from zero-valent carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc and platinum, the in-plane deviation of the conductive layer can be reduced even after the step of heating the conductive layer through molding processing, thereby making it possible to make the conductivity and electromagnetic wave shielding properties after molding excellent.
[0031] From the above viewpoint, by containing 60 mass % or more of particles, the component ratio of particles in the conductive layer can be increased, so the conductivity and electromagnetic shielding after molding can be improved. From the same viewpoint, it is more preferable to contain 65 mass % or more, and further preferably to contain 70 mass % or more.
[0032] In addition, by containing 91% by mass or less of particles, the component ratio of the resin in the conductive layer can be increased, thereby improving moldability. From the same viewpoint, it is more preferably contained at 87% by mass or less, and even more preferably contained at 85% by mass or less.
[0033] From the above viewpoints, the particles in the present invention preferably contain 65% to 87% by mass, and more preferably 70% to 85% by mass, when all components constituting the conductive layer are taken as 100% by mass.
[0034] From the viewpoint of improving the conductivity and electromagnetic wave shielding after molding, the particles of the present invention preferably contain one or more selected from zero-valent carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc and platinum, and from the viewpoint that the lower the resistivity, the better the conductivity and electromagnetic wave shielding, the particles of the present invention more preferably contain one or more selected from gold, silver, silver-plated copper powder, and alloys of silver and copper. "Zero-valent" refers not only to the carbon at the beginning, but also to all metal elements.
[0035] In the particles exemplified above, whether the particles contain a metal element of zero valence can be determined by performing energy dispersive X-ray spectroscopy Mapping analysis (hereinafter referred to as EDX Mapping analysis) on the cross section obtained by cutting the molded film for in-mold transfer, and judging whether the metal element of zero valence is detected in the particle part. EDX Mapping analysis can be performed, for example, using a scanning electron microscope (FEI company system, XL30 SFEG) with an energy dispersive X-ray spectrometer (EDAX company system, NEW XL30132-2.5) under the conditions of an accelerating voltage of 20kV and a magnification of 20000 times. In addition, the cutting device for the molded film for in-mold transfer can use "Cross Section Polisher" (registered trademark) SM-09010 (JEOL company system), etc. When using this device, an argon treatment is used for 10 hours under the conditions of an accelerating voltage of 4kV and a current value of 70μA to obtain a sample. In addition, with respect to carbon particles, it refers to particles that have been qualitatively analyzed by performing microscopic Raman Mapping analysis on the cross section obtained by the same method as above. Microscopic Raman Mapping analysis can be measured using, for example, a microscopic laser Raman spectrometer ("LabRAM" (registered trademark) HR Evolution, manufactured by Horiba, Ltd.).
[0036] Since the particles contain first particles having an aspect ratio of 1 or more and less than 2 and second particles having an aspect ratio of 2 or more, the overlap between particles in the conductive layer after molding can be maintained, and thus the electromagnetic shielding properties after molding can be further improved.
[0037] From the same viewpoint as above, when all components constituting the conductive layer are 100 mass %, the content of the first particles is preferably 20 mass % to 70 mass % and the content of the second particles is preferably 10 mass % to 60 mass %.
[0038] It should be noted that in the present invention, particles refer to primary particles. Therefore, the first particle refers to a primary particle having an aspect ratio of 1 or more and less than 2, and the second particle refers to a primary particle having an aspect ratio of 2 or more. As a method for calculating the average particle size of primary particles, for example, a scattering particle size distribution measuring device (manufactured by Horiba, Ltd., LA-960V2) can be used for calculation.
[0039] The so-called aspect ratio of the particles here can be calculated by the average major diameter / average minor diameter of the particles. As a method for calculating the average major diameter / average minor diameter of the particles, for example, a scanning electron microscope (manufactured by FEI, XL30 SFEG) is used to observe the cross section of the conductive layer obtained by cutting the molded film for in-mold transfer under the conditions of an accelerating voltage of 20 kV and a magnification of 100,000 times, extract 50 particles from the obtained image, approximate each particle to an ellipse, and calculate the aspect ratio by taking the average value of the maximum length as the average major diameter and the minimum length as the average minor diameter. In addition, as a cutting device for the molded film for in-mold transfer, for example, a manual rotary microscope slicer (manufactured by Leica Microsystems, "HistoCore BIOCUT" (registered trademark) R) can be used to obtain a sample.
[0040] In addition, by containing 40% by mass or less of resin, the component ratio of particles relative to all components constituting the conductive layer can be increased, so the conductivity and electromagnetic wave shielding after molding can be improved. From the same viewpoint, it is more preferred to contain 25% by mass or less, and further preferably to contain more than 20% by mass.
[0041] In addition, by containing 9% by mass or more of the resin, the dispersibility of the particles in the conductive layer and the moldability and flexibility of the conductive layer as a whole can be improved, thereby improving the moldability. From the same viewpoint, it is more preferable to contain 10% by mass or more, and further preferably to contain 13% by mass or more.
[0042] From the above viewpoints, the resin of the present invention preferably contains 10 mass % to 25 mass % of the resin in 100 mass % of the conductive layer, and more preferably contains 13 mass % to 20 mass % of the resin.
[0043] The weight average molecular weight of the resin is preferably 5,000 or more and less than 10,000 from the viewpoint of improving moldability and electrical conductivity and electromagnetic wave shielding properties after molding.
[0044] By making the weight average molecular weight of the resin above 5000, the viscosity of the resin becomes high, the fluidity of the conductive layer is stabilized in the molding process, and the in-plane deviation of the conductive layer can be reduced, so that the conductivity and electromagnetic wave shielding properties can be excellent. From the same point of view, it is more preferable to make the weight average molecular weight of the resin above 7500.
[0045] In addition, by making the weight average molecular weight of the resin less than 10000, the fluidity of the resin in the molding process is improved, and excellent moldability can be achieved. From the same viewpoint, the weight average molecular weight of the resin is more preferably 9000 or less, and further preferably 8500 or less.
[0046] From the above viewpoints, the weight average molecular weight of the resin of the present invention is more preferably 7,500 or more and 9,000 or less.
[0047] The weight average molecular weight of the resin can be calculated from the styrene-equivalent molecular weight measured by molecular weight distribution using the GPC method (gel permeation chromatography). The method for measuring the weight average molecular weight of the resin by the GPC method is as follows.
[0048] A device in which two separation columns (PLgel 5 μm MiniMIX-D, manufactured by Agilent Technologies, Ltd.) are connected in series on a high-speed GPC device (HLC-8220, manufactured by Tosoh Corporation) is used as a measuring device, and a polystyrene standard (weight average molecular weight: 5000, 10000, 30000) as a standard sample is placed in chloroform, stirred at 20°C for 10 minutes, and the standard sample solution filtered through a 0.45 μm membrane filter is measured to prepare a standard curve. Then, 5 mg of the conductive layer is placed in 2 mL of chloroform, stirred at 20°C for 10 minutes, and the sample filtered through a 0.45 μm membrane filter is provided for measurement, thereby calculating the weight average molecular weight of the resin. Here, the flow rate in the separation column is set to 0.35 mL / min, the column temperature is set to 40°C, and the detector uses a differential refractometer (RI detector, manufactured by Tosoh Corporation). In addition, by separating and acquiring each peak and weighing it, the content of each peak related to the resin can be grasped.
[0049] From the viewpoint of satisfying moldability, conductivity after molding, and electromagnetic wave shielding properties, the conductive layer of the present invention preferably has a glass transition temperature observed in the range of 40°C to 100°C when the temperature is increased from 20°C to 250°C at 20°C / min in a nitrogen atmosphere using a differential scanning calorimeter.
[0050] When the glass transition temperature of the conductive layer is observed at 100° C. or lower, flexibility can be sufficiently exhibited in the molding process, thereby achieving excellent moldability. From the same viewpoint, the glass transition temperature of the conductive layer is more preferably observed at 80° C. or lower.
[0051] In addition, by observing the glass transition temperature of the conductive layer at 40°C or above, the fluidity of the conductive layer is stabilized during the molding process, thereby reducing the in-plane deviation of the conductive layer, thereby making it possible to achieve excellent conductivity and electromagnetic wave shielding after molding. From the above viewpoint, it is more preferable to observe the glass transition temperature of the conductive layer at 60°C or above.
[0052] From these viewpoints, in the present invention, it is more preferable that the glass transition temperature of the conductive layer is observed at 60° C. or higher and 80° C. or lower.
[0053] The glass transition temperature of the conductive layer can be measured by a known differential scanning calorimeter. Specifically, a differential scanning calorimeter (Seiko Instruments Co., Ltd., RDC220) is used to measure and analyze the glass transition temperature of the conductive layer according to the following method in accordance with JIS K7121 (2012).
[0054] Only the conductive layer was cut from the molded film for in-mold transfer, and the obtained conductive layer was heated at 100°C for 4 hours in a nitrogen atmosphere, and then cooled to 25°C to prepare a 5 mg sample. The specific heat change based on the transition from the glass state to the rubber state when the sample was heated from 20°C to 250°C at 20°C / min in a nitrogen atmosphere was read. The midpoint glass transition temperature of the point where the straight line extending from each baseline and the straight line equidistant in the vertical axis (axis representing heat flow) direction intersected with the curve of the step-like change part of the glass transition was obtained and set as the glass transition temperature.
[0055] From the viewpoint of improving formability and electrical conductivity and electromagnetic wave shielding after molding, the aforementioned resin in the conductive layer preferably has polyester resin as the main component. The aforementioned resin in the conductive layer having polyester resin as the main component means that when the content of the aforementioned resin in the conductive layer is set to 100% by mass, it contains 50% by mass or more of polyester resin. By adopting this method, the softness of the resin and the dispersibility of the particles can be improved, so that the formability and electrical conductivity and electromagnetic wave shielding after molding can be excellent. From the same viewpoint, when the content of the aforementioned resin is set to 100% by mass, it is more preferred to contain 80% by mass or more of polyester resin. In addition, from the above viewpoint, the resin contained in the conductive layer is further preferably a polyester resin. In addition, from the same viewpoint, it is preferred that the aforementioned polyester resin is a saturated polyester resin, and from the viewpoint of durability, it is further preferred that the aforementioned polyester resin is a thermoplastic saturated polyester resin.
[0056] The polyester resin preferably has an acid value of 5 mgKOH / g or more and 20 mgKOH / g or less from the viewpoint of improving moldability and electrical conductivity and electromagnetic wave shielding properties after molding.
[0057] By making the acid value of the polyester resin 5 mgKOH / g or more, the adhesion with the release layer is improved, thereby reducing the in-plane deviation of the conductive layer after the molding process, thereby making it possible to achieve excellent conductivity and electromagnetic wave shielding properties. From the same viewpoint, it is more preferable to make the acid value of the polyester resin 7 mgKOH / g or more.
[0058] In addition, by setting the acid value of the polyester resin to 20 mgKOH / g or less, the dispersibility of the particles and the polyester resin is improved, thereby achieving excellent moldability. From the same viewpoint, it is more preferable to set the acid value of the polyester resin to 15 mgKOH / g or less.
[0059] From the above viewpoints, it is more preferred that the acid value of the polyester resin be 5 mgKOH / g or more and 20 mgKOH / g or less and the weight average molecular weight be 7500 or more and 9000 or less.
[0060] The qualitative / quantitative analysis method of polyester resin can be, for example, the following method: only the conductive layer is scraped off from the molded film for in-mold transfer, a sample of the obtained conductive layer is freeze-dried, and the recovered dry solid is qualitatively / quantitatively analyzed by gas chromatography-mass spectrometry (P&T-GC / MS) equipped with a purge and trap sampler (heating desorption device).
[0061] The acid value of the polyester resin can be measured according to the titration method of JIS K 5601-2-1 (1999). Specifically, for example, a sample can be dissolved in a mixed solvent of toluene / ethanol = 2 / 1 by volume, and phenolphthalein is used as an indicator and titrated with a potassium hydroxide solution, and the acid value can be measured according to the titration method of JIS K 5601-2-1 (1999) calculated using the following formula.
[0062] Acid value (mgKOH / g) = 56.1 × V × C / m
[0063] V: titration amount (ml), C: concentration of titration solution (mol / 1), m: solid content mass of the sample (g).
[0064] From the viewpoint of satisfying the conductivity and electromagnetic wave shielding after the molding process, the thickness of the conductive layer of the present invention is preferably 5 μm or more and 15 μm or less. By making the thickness of the conductive layer less than 15 μm, the conductive layer can be stably heated in the molding process, thereby reducing the in-plane deviation of the conductive layer, and thus the conductivity and electromagnetic wave shielding after the molding process can be excellent. From the same viewpoint, the thickness of the conductive layer is more preferably less than 12 μm. In addition, by making the thickness of the conductive layer more than 5 μm, the particle content in the conductive layer increases, and the resistivity of the conductive layer becomes low, so that the conductivity and electromagnetic wave shielding can be fully exerted, and the conductivity and electromagnetic wave shielding after the molding process can be excellent. From the same viewpoint, the thickness of the conductive layer is more preferably more than 7 μm.
[0065] [Electromagnetic wave shielding properties]
[0066] The molded film for in-mold transfer of the present invention can achieve an electromagnetic wave shielding effect of 40 dB or more when measured by the KEC method (electric field) using electromagnetic waves with a frequency of 300 MHz by adopting the above-mentioned embodiment.
[0067] The KEC method is a measurement method specified by the Kansai Electronic Industry Promotion Center (Finance), which is a method for evaluating the shielding effect of electromagnetic waves generated in the near field by dividing them into electric fields and magnetic fields. The measurement using this method can be implemented by receiving electromagnetic waves sent from a transmitting antenna (transmitting fixture) via an electromagnetic wave shielding film (measurement sample) and using a receiving antenna (receiving fixture). In the KEC method, the electromagnetic waves passing through (through) the electromagnetic wave shielding film in the receiving antenna are measured. That is, since the electromagnetic wave (signal) transmitted is measured by the electromagnetic wave shielding film, how much it is attenuated on the receiving antenna side, the electromagnetic wave shielding property of blocking (shielding) the electromagnetic wave is obtained by adding up the reflected component of the reflected electromagnetic wave and the absorbed component of the absorbed electromagnetic wave.
[0068] The in-mold transfer molding film of the present invention preferably has an electromagnetic wave shielding effect of 40 dB or more when measured by the KEC method (electric field) using electromagnetic waves having a frequency of 300 MHz.
[0069] [Mold release layer]
[0070] The release layer of the present invention is not particularly limited as long as it is a layer for peeling off the conductive layer and the base film. From the viewpoint of achieving good productivity, it is preferred that the main component be silicone resin. By making the main component of the release layer silicone resin, and more preferably making the content of the silicone resin in the release layer 80% by mass or more, the adhesion between the base film and the conductive layer can be controlled, so that the processability of the conductive layer and the peelability of the base film in the molding process can be taken into account.
[0071] As the silicone resin, from the viewpoint of controlling the adhesion with the conductive layer, modified silicone produced by graft polymerization with an organic resin, i.e., polyester-modified silicone resin, acrylic-modified silicone resin, polyurethane-modified silicone resin, epoxy-modified silicone resin, alkyd-modified silicone resin, is more preferred. From the viewpoint of being able to control the adhesion with the polyester resin, alkyd-modified silicone resin is further preferred.
[0072] [Base film]
[0073] The substrate film of the present invention is preferably a plastic film made of polyester, such as polyethylene terephthalate, polyethylene 2,6-naphthalate, polyethylene α,β-bis(2-chlorophenoxy)ethane 4,4'-dicarboxylate, polybutylene terephthalate, etc., from the viewpoint of good dimensional stability and durability and improved productivity. Among them, a film made of polyethylene terephthalate is particularly preferred from the viewpoint of excellent processability in the lamination and molding steps of the release layer and the conductive layer, and biaxially stretched polyethylene terephthalate is most preferred from the same viewpoint.
[0074] [Film for in-mold transfer]
[0075] The molded film for in-mold transfer of the present invention has excellent moldability and electrical conductivity and electromagnetic wave shielding properties after molding, so it is easy to add a conductive and electromagnetic wave shielding layer to a molded product having a curved surface, concave-convex ribs, hinges, protrusions, or a hollow shape. That is, since the in-plane deviation of the electrical conductivity and electromagnetic wave shielding is small, it can be more appropriately used as an in-mold transfer molded film for imparting electrical conductivity and electromagnetic wave shielding properties to a molded product, and in particular, since the in-plane deviation of the electromagnetic wave shielding is small, it can be further appropriately used as an in-mold transfer molded film for imparting electromagnetic wave shielding properties to a molded product.
[0076] From the above viewpoints, the use is not limited as long as the effects of the present invention are not impaired, and for example, it can be suitably used to impart electromagnetic wave shielding properties to personal computers, displays, OA equipment, mobile phones, portable information terminals, optical equipment, audio equipment, air conditioners, lighting equipment, entertainment equipment, toys, other home appliances, electronic equipment, semiconductor components, electrical components and internal parts of automobiles, electrical components and internal parts of aircraft, electrical components and internal parts of two-wheeled vehicles, etc.
[0077] From the viewpoint of bonding the conductive layer to the resin and / or resin precursor, the molded film for in-mold transfer of the present invention preferably comprises a base film, a release layer, a conductive layer, and an adhesive layer in this order, with the adhesive layer being the outermost layer.
[0078] In the in-mold transfer forming film of the present invention, the resin used in the adhesive layer, that is, the resin contained in the adhesive layer can be a heat-sensitive resin or a pressure-sensitive resin, and the raw material of the adhesive layer can be appropriately selected according to the material of the resin and / or the resin precursor.
[0079] The resin contained in the adhesive layer is preferably an acrylic resin, a polyester resin, a polyphenylene ether / polystyrene resin, a polycarbonate resin, a polystyrene resin, a styrene copolymer resin, a polyamide resin, a chlorinated polyolefin resin, a chlorinated vinyl acetate copolymer resin, a cyclized rubber, a coumarone-indene resin, etc., used alone or in combination.
[0080] [Method for producing molded film for in-mold transfer]
[0081] The method for producing the molded film for in-mold transfer includes, for example, the materials, amounts used, treatment contents, and treatment steps exemplified below.
[0082] The molded film for in-mold transfer of the present invention can be produced, for example, by sequentially coating a coating material composition for a release layer and a coating material composition for a conductive layer on one surface of a substrate film and subjecting the resulting film to heat treatment.
[0083] The coating material composition of the release layer in the present invention can be obtained by mixing a silicone resin and an organic solvent. For the organic solvent used in the coating material composition of the release layer in the present invention, when all the components of the resin mixture constituting the silicone resin and the organic solvent are set to 100% by mass, from the viewpoint of making the coating property of the substrate film good, it is preferred that the organic solvent is 50% by mass or more and 99% by mass or less. From the viewpoint of improving the coating property of the coating material composition of the release layer, organic solvents such as ethyl methyl ketone, methyl isobutyl ketone, butyl acetate, ethyl acetate, methanol, isopropanol, cyclohexanone, toluene, xylene, etc. can be cited. In addition, in the coating material composition, as long as the effect of the present invention is not impaired, inorganic particles, organic particles, leveling agents, etc. can be mixed from the viewpoint of preventing adhesion when winding into a film roll and improving the coating property of the substrate film.
[0084] The coating material composition of the conductive layer in the present invention can be obtained by obtaining a resin mixture obtained by mixing particles, resin and a mixed organic solvent, and then mixing a diluting organic solvent. For the particles used in the resin mixture in the present invention, when the total components consisting of the particles and the resin are set to 100% by mass, it is preferred that the particles are 60% by mass or more and 91% by mass or less. In addition, for the resin used in the resin mixture in the present invention, when the total components consisting of the particles and the resin are set to 100% by mass, it is preferred to contain a resin of 9% by mass or more and 40% by mass or less. For the mixed organic solvent used in the resin mixture of the conductive layer in the present invention, when the total components of the resin mixture constituting the particles, the resin and the mixed organic solvent are set to 100% by mass, from the viewpoint of making the mixed dispersion of the particles and the resin good, it is preferred that the mixed organic solvent is 5% by mass or more and 50% by mass or less. From the viewpoint of suppressing the volatilization of the organic solvent for mixing when the particles and the resin are mixed and suppressing the viscosity increase of the resin mixture, the organic solvent for mixing is preferably N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, dimethylimidazolidinone, dimethyl sulfoxide, γ-butyrolactone, ethyl lactate, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, ethylene glycol mono-n-propyl ether, diacetone alcohol, tetrahydrofurfuryl alcohol, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether acetate (hereinafter referred to as "DMEA"), diethylene glycol monobutyl ether, diethylene glycol, and 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, used alone or in combination.
[0085] For the dilution organic solvent in the present invention, when all the components of the resin composition composed of the resin mixture and the dilution organic solvent are set to 100 mass%, from the viewpoint of taking into account the coating property when the conductive layer is coated on the release layer and the thickness of the conductive layer, it is preferred that the dilution organic solvent is 10 mass % or more and 80 mass % or less. Examples of the mixed organic solvent include ethyl methyl ketone, methyl isobutyl ketone, butyl acetate, ethyl acetate, methanol, isopropanol, cyclohexanone, toluene, xylene, etc.
[0086] The method for mixing the particles, polyurethane resin and mixing organic solvent in the resin mixture of the present invention can use, for example, well-known mixing and dispersing methods such as a three-roll mill, an ultrasonic disperser, a sand mill, a clay dry crusher, a coarse crusher, an ultrafine crusher, a ball mill, an impeller, a disperser, a KD mill, a colloid mill, a negative resistance tube, a planetary mill and a pressure kneading machine.
[0087] The resin mixture and the diluting organic solvent in the resin composition may be mixed using a known mixing and dispersing method such as a magnetic stirrer, a homodispersor, ultrasonic irradiation, vibration dispersion, and manual mixing and dispersing.
[0088] As a method for sequentially coating a coating material composition for a release layer and a coating material composition for a conductive layer on a single side of a substrate film, it is preferred to form the release layer and the conductive layer by coating using a comma coating method, an applicator method, a dip coating method, a roller coating method, a wire rod coating method, a reverse coating method, a kiss coating method, a gravure coating method or a die coating method (U.S. Patent No. 2,681,294), and from the viewpoint of processability, an applicator method, a comma coating method, a reverse coating method and a die coating method are further preferred.
[0089] The molded film for in-mold transfer of the present invention is excellent in moldability and in conductivity and electromagnetic wave shielding properties after molding, and has good productivity, so it is preferably used for in-mold transfer.
[0090] That is, it is preferably used for a method for producing a molded article, the method comprising the steps of placing a molding film for in-mold transfer in a mold and then injecting a resin and / or a resin precursor.
[0091] This process can be performed using a known injection molding machine and a film feeder. For example, as the injection molding machine, S-2000 (manufactured by Fanuc Co., Ltd.) can be used, and as the film feeder, a roll foil punching machine (manufactured by Hori Gold Leaf Powder Co., Ltd.) can be used.
[0092] [Production method of molded products: In-mold transfer injection molding]
[0093] The method for producing a molded article of the present invention can preferably adopt an embodiment including the step of placing a molding film for in-mold transfer in a mold and then injecting a molding resin and / or a molding resin precursor.
[0094] Specifically, for example, a method for obtaining a molded product in the following order can be preferably adopted: the molding film for in-mold transfer of the present invention is passed through the mold of an injection molding machine, the conductive layer side of the aforementioned molding film is arranged in a manner facing the cavity of the mold for in-mold transfer injection molding, and an injection resin is injection molded thereon as a molding resin and / or a molding resin precursor, thereby transferring the conductive layer of the aforementioned molding film to the surface of the injection resin, and after the injection resin is cooled, the injection molding mold is opened and the base film of the aforementioned molding film is peeled off.
[0095] The molding resin and / or molding resin precursor of the present invention is preferably a thermoplastic resin or an elastomer, and more preferably a resin such as polybutylene terephthalate (PBT), polyphenylene sulfide, polycarbonate, polyacetal, polyethylene terephthalate, polyphenylene ether, polyacrylate, polyamide, polypropylene, acrylic, polystyrene, polyacrylonitrile-styrene, polyacrylonitrile-butadiene-styrene (ABS), epoxy resin, etc., is used alone or in combination. In addition, glass fiber, inorganic filler, etc. may be appropriately added to the resin as a reinforcing material.
[0096] Example
[0097] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0098] In addition, the measuring method and the evaluation method in this Example are as follows.
[0099] (1) Thickness of the conductive layer and adhesive layer
[0100] The thickness (μm) of the conductive layer and the adhesive layer was determined as follows: using a manual rotating microscope microtome (manufactured by Leica Microsystems, "HistoCore BIOCUT" (registered trademark) R), the molded film for in-mold transfer was cut in a direction perpendicular to the thickness to obtain a cross section of the molded film for in-mold transfer, and the cross section of the conductive layer was observed using a scanning electron microscope (manufactured by FEI, XL30 SFEG) at an acceleration voltage of 20 kV and an observation magnification of 100,000 times, and five arbitrary locations were measured based on the cross-sectional photograph, and the average value of the obtained values was calculated.
[0101] (2) Particle aspect ratio
[0102] In the method of (1), 50 particles are extracted from the obtained scanning electron microscope image, each particle is approximated as an ellipse, the maximum length is taken as the major diameter, the minimum length is taken as the minor diameter, and the aspect ratio of each particle is calculated. Then, the obtained aspect ratio is used to make a histogram at a scale of 0.1, and the value of the peak is calculated as the aspect ratio of the second particle. In the case of two peaks, the peak with a smaller value is taken as the aspect ratio of the first particle, and the peak with a larger value is taken as the aspect ratio of the second particle.
[0103] (3) Glass transition temperature of the conductive layer
[0104] The measurement and analysis were performed by the following method based on JIS K7121 (2012) using a differential scanning calorimeter (RDC220 manufactured by Seiko Instruments Co., Ltd.).
[0105] Take 5 mg of the conductive layer or thermoplastic resin as a sample. When evaluating the conductive layer or thermoplastic resin, heat the conductive layer or thermoplastic resin at 100°C for 4 hours in a nitrogen atmosphere, cool it to 25°C, and prepare a 5 mg sample. Read the change in specific heat based on the transition from the glass state to the rubber state when the sample is heated from 20°C to 250°C at 20°C / min in a nitrogen atmosphere. Calculate the midpoint glass transition temperature where a straight line extending from each baseline at an equal distance in the direction of the vertical axis (axis representing heat flow) intersects the curve of the step-shaped change portion of the glass transition, and set it as the glass transition temperature.
[0106] (4) Weight average molecular weight of resin
[0107] The molecular weight analysis of the thermoplastic resin contained in the conductive layer was performed by the following method, and the weight average molecular weight was evaluated based on the detected peak area.
[0108] <Molecular weight analysis method>
[0109] A device in which two separation columns (PLgel5μm MiniMIX-D, manufactured by Agilent Technologies, Ltd.) are connected in series on a high-speed GPC device (HLC-8220, manufactured by Tosoh Corporation) is used as a measuring device, and a polystyrene standard (weight average molecular weight: 5000, 10000, 30000) as a standard sample is placed in chloroform, stirred at 20°C for 10 minutes, and the standard sample solution filtered through a 0.45μm membrane filter is measured to prepare a standard curve. Then, 5mg of the conductive layer is placed in 2mL of chloroform, stirred at 20°C for 10 minutes, and the sample filtered through a 0.45μm membrane filter is provided for measurement. Here, the flow rate in the separation column is set to 0.35mL / min, the column temperature is set to 40°C, and the detector uses a differential refractometer (RI detector, manufactured by Tosoh Corporation).
[0110] (5) Electromagnetic wave shielding effect of molded films for in-mold transfer
[0111] The molded film for in-mold transfer was cut into 120 mm × 120 mm, measured using the KEC method (electric field), and the electromagnetic wave shielding effect (dB) at a frequency of 300 MHz was calculated using a spectrum analyzer. The obtained result was taken as the electromagnetic wave shielding effect of the molded film for in-mold transfer. The higher the electromagnetic wave shielding effect, the better the electromagnetic wave shielding property.
[0112] (6) Electromagnetic shielding effect of the molded film for in-mold transfer when stretched 1.1 times in the longitudinal direction and 1.1 times in the transverse direction
[0113] The molded film for in-mold transfer was cut into 120 mm × 120 mm, and the molded film for in-mold transfer was biaxially stretched at 1.1 times in the longitudinal direction × 1.1 times in the transverse direction using LAB-STRETCHING KARO5.0 manufactured by Brueckner Company to prepare a sample, and the KEC method (electric field) was used for measurement, and the electromagnetic wave shielding effect (dB) at a frequency of 1 GHz was measured using a spectrum analyzer, and the obtained result was used as the electromagnetic wave shielding effect at a frequency of 1 GHz. The higher the electromagnetic wave shielding effect, the better the electromagnetic wave shielding property.
[0114] (7) Processing adaptability of the molding process
[0115] After the film roll of the molding film for in-mold transfer is installed in the film feeder, namely the roller foil punching machine (Hori Gold Leaf Powder Co., Ltd.) of the injection molding machine ROBO SHOT S20000i 150A (produced by Fanuc Co., Ltd.), it passes through the injection molding mold, and the conductive layer side of the molding film for in-mold transfer is arranged in a manner facing the cavity of the in-mold transfer injection molding mold (a tile-shaped molded product with a width of 30 mm, a length of 300 mm, and a height of 10 mm, and the temperature during processing: 80°C). The molded product was obtained in the following order: polybutylene terephthalate resin ("TRECON" (registered trademark) 1101G manufactured by Toray Industries, Ltd.) was used as molding resin A, and polyacrylonitrile-butadiene-styrene resin ("TOYOLAC" (registered trademark) 100 manufactured by Toray Industries, Ltd.) was used as molding resin B, and these molding resins were used as injection resins for injection molding, thereby transferring the conductive layer of the molding film for in-mold transfer to the surface of the injection resin, and after cooling, the injection molding mold was opened to peel off the base film of the molding film for in-mold transfer. Based on the state of the conductive layer when the injection molding mold was opened, the processing adaptability of the molding process was evaluated according to the following criteria.
[0116] It should be noted that when polybutylene terephthalate resin ("TRECON" (registered trademark) 1101G manufactured by Toray Industries, Ltd.) is used as molding resin A, the melting temperature of the injection resin is 260°C, the injection speed is 8 mm / second, and the cooling time is 25 seconds. When polyacrylonitrile-butadiene-styrene resin ("TOYOLAC" (registered trademark) 100 manufactured by Toray Industries, Ltd.) is used as molding resin B, the melting temperature of the injection resin is 230°C, the injection speed is 8 mm / second, and the cooling time is 25 seconds.
[0117] A: There is no abnormality between the molded product and the base film, and the conductive layer is transferred to the surface of the molded product.
[0118] B: After the injection molding die is opened, the conductive layer transferred to the surface of the molded product is uneven, or the portion of the molded product surface to which the conductive layer is to be transferred to which the conductive layer is not transferred is less than 20%.
[0119] C: The conductive layer is not transferred to 20% or more of the surface of the molded article to which the conductive layer is to be transferred.
[0120] (8) Formability of film for in-mold transfer
[0121] In the method of (7), the injection molding die was opened, and the molded film for in-mold transfer was visually observed before the base film of the molded film for in-mold transfer was peeled off, and evaluation was performed based on the following criteria.
[0122] A: The conductive layer and the base film fit the molded product. This is a good result.
[0123] B: The conductive layer and the base film fit the molded article, but cracks appear in part of the conductive layer or the base film. No practical problem.
[0124] C: The conductive layer and the base film do not fit the molded product. Or cracks appear on the conductive layer or the base film. It is not practical.
[0125] (9) Uneven thickness of the conductive layer
[0126] Regarding the uneven thickness of the conductive layer, the molded article obtained by the method of (7) was cut at any five locations in a direction perpendicular to the thickness of the molded article using a manual rotating microscope slicer (manufactured by Leica Microsystems, "HistoCore BIOCUT" (registered trademark) R) to obtain a cross section of the molded article. The cross section of the conductive layer was observed using a scanning electron microscope (manufactured by FEI Company, XL30 SFEG) at an accelerating voltage of 20 kV and an observation magnification of 100,000 times, and the standard deviation of the measured values was calculated and evaluated according to the following criteria.
[0127] A: The standard deviation is 1.5 or less, which is a good result.
[0128] B: The standard deviation is greater than 1.5 and is 2.5 or less, which is not a practical problem.
[0129] C: The standard deviation is greater than 2.5 and is not practical.
[0130] (10) In-plane variation of electromagnetic shielding effect
[0131] The electromagnetic shielding effect (dB) at a frequency of 300 MHz was calculated using a spectrum analyzer at 5 random locations of the molded article obtained by the method (7). The measured values were evaluated according to the following criteria.
[0132] A: The difference between the maximum value and the minimum value is 5 or less, which is a good result.
[0133] B: The difference between the maximum value and the minimum value is greater than 5 and less than 10, which is not a practical problem.
[0134] C: The difference between the maximum and minimum values is greater than 10, which is not practical.
[0135] The materials used are as follows.
[0136] (Silicone resin A)
[0137] Alkyd-modified silicone resin (X-62-900B manufactured by Shin-Etsu Chemical Co., Ltd.).
[0138] (Silicone resin B)
[0139] Addition reaction type silicone resin ("DOWSIL" (registered trademark) LTC750A manufactured by Dow Toray Corporation).
[0140] (Particle A)
[0141] Silver particles (AgG-204B manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., average particle size 1.8 μm, kidney-shaped, aspect ratio 2.2).
[0142] (Particle B)
[0143] Silver particles (manufactured by Dowa Electronics Co., Ltd., AG-2-1C, average particle size 0.8 μm, spherical, aspect ratio 1.0).
[0144] (Polyester resin A)
[0145] Saturated copolymer polyester resin (manufactured by UNITIKA Corporation, "ELITEL" (registered trademark) XA-0847, glass transition temperature 58°C, weight average molecular weight 8000, acid value 10 mg / KOH).
[0146] (Polyester resin B)
[0147] Polyurethane-modified polyester resin (manufactured by Toyobo Co., Ltd., "BYRON" (registered trademark) UR-4800, glass transition temperature 106° C., weight average molecular weight 25,000, acid value 4 mg / KOH).
[0148] (Polyester resin C)
[0149] Saturated copolymer polyester resin (manufactured by UNITIKA Corporation, "ELITEL" (registered trademark) UE-3320, glass transition temperature 38°C, weight average molecular weight 1800, acid value 1 mg / KOH).
[0150] (Polyester resin D)
[0151] Saturated copolymer polyester resin (manufactured by Toyobo Co., Ltd., "BYRON" (registered trademark) GK-810, glass transition temperature 46°C, weight average molecular weight 6000, acid value 5 mg / KOH).
[0152] (Polyester resin E)
[0153] Saturated copolymer polyester resin (manufactured by UNITIKA Corporation, "ELITEL" (registered trademark) KA-5034, glass transition temperature 67°C, weight average molecular weight 9000, acid value 7 mg / KOH).
[0154] (Acrylic resin)
[0155] Acrylic resin (manufactured by Daisei Fine Chemicals Co., Ltd., 8DL-100, glass transition temperature 90° C., weight average molecular weight 8,000, acid value 1 mg / KOH).
[0156] (Injection resin A)
[0157] Polybutylene terephthalate resin ("TRECON" (registered trademark) 1101G manufactured by Toray Industries, Inc.).
[0158] (Injection resin B)
[0159] Polyacrylonitrile-butadiene-styrene resin ("TOYOLAC" (registered trademark) 100 manufactured by Toray Industries, Inc.).
[0160] [Example 1]
[0161] <Production of Release Layer Laminated Film>
[0162] The materials of the release layer composition shown in Table 1 were dissolved in methyl ethyl ketone, and the raw materials were mixed and dispersed using a homogenizer (manufactured by PRIMIX Co., Ltd.) to obtain a release layer coating composition having a solid content of 3.0% by mass. As a substrate film, a biaxially stretched polyethylene terephthalate film having a thickness of 38 μm ("Lumirror" (registered trademark) S10 manufactured by Toray Industries, Inc.) was used. The release layer coating composition was applied by a gravure coating method, and after drying at 120°C, a release layer laminated film having a release layer having a thickness of 0.05 μm was obtained, which was wound into a roll.
[0163] <Production of molding film for in-mold transfer>
[0164] The raw materials for obtaining the conductive layer are set to the composition of Table 1, dispersed or dissolved in DMEA as an organic solvent, and kneaded using a three-roll mill to obtain a resin mixture for the conductive layer. Next, the resin mixture and ethyl methyl ketone are mixed and dispersed using a homogenizer (manufactured by PRIMIX Co., Ltd.) to obtain a conductive layer coating composition having a solid content of 30.0% by mass. On the release layer of the release layer laminated film, the conductive layer coating composition is applied by gravure coating, dried at 120°C, and a conductive layer having a thickness of 10 μm is laminated. Furthermore, the adhesive layer coating composition (vinyl chloride-vinyl acetate copolymer adhesive K588HP manufactured by Toyo Ink Co., Ltd.) is applied by gravure coating, dried, and cured, and an adhesive layer having a thickness of 10 μm is laminated to obtain a molded film for in-mold transfer, which is wound into a roll.
[0165] <Production of molded products>
[0166] The molded article was produced by the method described in "(7) Processability of the molding step". The obtained conductive layer, resin, molded film for in-mold transfer and molded article were evaluated for various evaluation items. The evaluation results are shown in Table 1.
[0167] [Examples 2 to 11, Comparative Examples 1 to 3]
[0168] A molded film for in-mold transfer and a molded article were prepared in the same manner as in Example 1 except that the mold release layer, particles, resin, injection resin, and adhesive layer were as described in Tables 1 and 2. In addition, no mold release layer was provided in Comparative Example 1. The evaluation results of the molded film for in-mold transfer and the molded article are shown in Tables 1 and 2.
[0169] [Table 1]
[0170]
[0171] [Table 2]
[0172]
Claims
1. A molded film for in-mold transfer, comprising a substrate film, a release layer, and a conductive layer in this order, wherein the conductive layer contains 60% by mass or more and 91% by mass or less of particles in 100% by mass of the conductive layer, the conductive layer contains 9% by mass or more and 40% by mass or less of a resin, the weight average molecular weight of the resin is 5000 or more and less than 10000, and the particles contain one or more selected from zero-valent carbon, silver, gold, copper, nickel, chromium, palladium, indium, aluminum, zinc, and platinum.
2. The molded film for in-mold transfer according to claim 1, wherein The conductive layer has a thickness of 5 μm or more and 15 μm or less.
3. The molded film for in-mold transfer according to claim 1 or 2, wherein When the temperature of the conductive layer is increased from 20° C. to 250° C. at 20° C. / min in a nitrogen atmosphere using a differential scanning calorimeter, a glass transition temperature is observed in the range of 40° C. to 100° C. 4 . The molded film for in-mold transfer according to claim 1 , comprising the base film, the release layer, the conductive layer, and an adhesive layer in this order.
5. The molded film for in-mold transfer according to claim 1 or 2, wherein The release layer contains silicone resin as a main component.
6. The molded film for in-mold transfer according to claim 5, wherein The demoulding layer has alkyd-modified silicone resin as a main component.
7. The molded film for in-mold transfer according to claim 1 or 2, wherein The resin is a polyester resin.
8. The molded film for in-mold transfer according to claim 7, wherein The acid value of the polyester resin is 5 mgKOH / g or more and 20 mgKOH / g or less.
9. The formed film for in-mold transfer according to claim 1 or 2, wherein The particles include first particles having an aspect ratio of 1 or more and less than 2 and second particles having an aspect ratio of 2 or more.
10. The molded film for in-mold transfer according to claim 1 or 2, wherein The electromagnetic wave shielding effect of the molded film for in-mold transfer measured by the KEC method (electric field) using electromagnetic waves with a frequency of 300 MHz is 40 dB or more.
11. The molded film for in-mold transfer according to claim 1 or 2, wherein The substrate film is a polyethylene terephthalate film.
12. A method for producing a molded article, comprising the steps of placing the molded film for in-mold transfer according to claim 1 or 2 in a mold and then injecting a molding resin and / or a molding resin precursor.
Citation Information
Patent Citations
Method of coating strip material
US2681294A
Transfer film for in-mold molding and in-mold molded product having electromagnetic wave shielding properties
JP2006297642A
Transfer foil for in-mold having embossed layer serving also as hard coat layer, method of manufacturing the same and injection molded article
JP2012201016A
Transfer film, and method for producing transparent electroconductive laminate
JP2014221522A
Conductor-containing transfer film, conductor-containing transfer layer adhered resin molded body and manufacturing method therefor
JP2018069525A